Mobility and transition of Nymphalidae between Premontane Rainforest Fragments and Agroforestry Matrix (Melgar, Tolima, Colombia) (Insecta: Lepidoptera) - Torres-Martínez, Adriana; Dumar, Juan C. (SHILAP Revista de lepidopterología, 2024)
The matrix in fragmented landscapes is considered as one of the major limitations in conservation research, because it is considered as a non-habitat. The present study was developed in Tolima (Colombia), with the objective of evaluating the mobility and transition of Nymphalidae between the forest fragment, the edge and outside (agroforestry matrix). Nymphalidae were used as a study model to evaluate the mobility and transition between landscape units and the influence of the edge effect on butterflies. We calculated and statistically compared abundance and richness in three sampling zones at three distances from the edge (130 m, 65 m and 50 m), using standardized methodologies (Jama and Van Someren Rydon Traps). The collected specimens (43 recaptures) were marked, photographed and released according to the capture-recapture method. Our results suggest that individuals moved more frequently from the forest fragment to the MA (67%), which is evidence of the permeability of the edge and the interaction between these two coverages. Significant differences are evident between the two coverages in relation to richness and abundance and based on the distances evaluated according to their diversity, suggesting an edge effect at least up to 50 meters from the matrix area. In this sense, the presence of rare and indicator species and a strong effect on specialist Lepidoptera, which can be key to develop conservation plans, were evidenced.